The Development of E-Learning Media by Using Eduflow Application Spermatophyta Material - Izmanah Fajriatun; Evi Roviati (Tarbiyah : Jurnal Ilmiah Kependidikan, 2022)
Along with the development of science and technology, the use of ICT is also carried out in Biology learning. This ICT utilization can be in the form of eduflow-based learning media. This study aims to know validity of eduflow based learning media, understanding and media feasibility from student responses. The development model used was the Sugiyono development model with several stages in research and development. The data collection technique used was a questionnaire with descriptive quantitative data analysis. Before being mass-produced, validation of the feasibility of the media was carried out by the material experts with the percentage at 92% (very good) and learning media with the percentage 88% (very good). After revision, the media was tested in a small group of 16 students of the 10th science grade. The result of the analysis showed that the eduflow-based learning media is classified as very good so this media is suitable for use in the Biology Spermatophyta material.